2021
DOI: 10.1088/1742-6596/1776/1/012018
|View full text |Cite
|
Sign up to set email alerts
|

How are Students’ Conceptual Understanding for Solving Mathematical Problem?

Abstract: This study describes students’ conceptual understanding in solving mathematical problems. Conceptual understanding is an important component in learning mathematics. By learning mathematics students are able to apply concepts and think logically. The qualitative research took students of SMP Negeri 1 Gatak Sukoharjo Indonesia. There were 59 students who were tested to find out the conceptual understanding. All students are categorized into 16 students with high mathematical ability (Subject S-1), 25 students w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 6 publications
0
8
0
1
Order By: Relevance
“…Students can create such illustrations using software, in this case GeoGebra. This is relevant to the research of Fatahillah, Puspitasari and Hussen (2020), in which GeoGebra is helpful to improve both students' performances and conceptual understanding (Kholid, Imawati, Swastika, Maharani & Pradana, 2021). It is because GeoGebra provides perfect visualization in geometry (Sholihah & Maryono, 2020).…”
Section: Discussionmentioning
confidence: 85%
“…Students can create such illustrations using software, in this case GeoGebra. This is relevant to the research of Fatahillah, Puspitasari and Hussen (2020), in which GeoGebra is helpful to improve both students' performances and conceptual understanding (Kholid, Imawati, Swastika, Maharani & Pradana, 2021). It is because GeoGebra provides perfect visualization in geometry (Sholihah & Maryono, 2020).…”
Section: Discussionmentioning
confidence: 85%
“…Therefore, they act as facilitators, guiding students through the learning process while allowing them to shape their understanding of the instruction (Rhodes & Bellamy, 1999, as cited in Shimamoto, 2012. With the use of the flipped classroom, the teacher's role shifts from knowledge provider to learning facilitator, and the student's role shifts from information collector to the active practitioner (Ameyaw et al, 2019;Kenney & Kastberg, 2013;Kholid et al, 2021) In terms of Bloom's taxonomy of learning, the flipped classroom has students perform the lower levels of cognitive work outside of class, and the higher levels of cognitive work in class, alongside their fellow students and instructor (Abeysekera & Dawson, 2015). The teacher serving as a facilitator and curator in a constructivist sense (Altaftazani et al, 2020;Bada & Olusegun, 2015) provides an opportunity for students to gain first exposure to the course material prior to the lesson in the form of videos or audios.…”
Section: Educational Implicationsmentioning
confidence: 99%
“…The results of the study showed a consistent rise in those three components of CU, which practically supports the integration between mental processes and understanding of mathematical ideas along with knowledge of the relationships between concepts through explanation, interpretation, and application, as well as linking previous knowledge with the newly acquired one. This is due to what was confirmed by Kholid et al (2021) in their definition of CU, and what is included in definition of Jaber (2003) and Tolba (2009).…”
Section: Discussionmentioning
confidence: 72%